O Direito de Ingerência Ecológica dos Estados - Silvana Colombo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2007)
There it is the ecological crisis: risks of increase the damage in the ozone layer chemistry and radioactive pollution, deforestation only are some examples of the environmental treat which is upon the planet. Therefore the environmental management have to be recognized in the cases of major ecological damage risks. That right inflict in the inefficiency of the environment protection provided by the state or when one can not divide this responsibility with the natives. The management of a state in the other territories, in a ecological matter, have the function of prevent the possibility of a damage to the environment or then minimize those effects.